The psychomotor vigilance test: a comparison of different test durations in elite athletes - Jones, M. J.; Dunican, I. C.; Murray, K.; Peeling, P.; Dawson, B.; Halson, S.; Miller, J.; Eastwood, P. R. (Journal of Sports Sciences, 2018)
The 10-min Psychomotor Vigilance Test (PVT-10) is regarded as the gold-standard for assessing vigilant attention following sleep loss; however, other studies have investigated whether shorter versions of the test elicit similar results to the PVT-10. The present study compared the PVT-10 with 3-min (PVT-3) and 5-min (PVT-5) versions of the test in elite female basketball players. Athletes performed all three tests in the morning and evening for seven consecutive days. Response speed (mean reciprocal reaction time; mean 1/RT), number of errors and number of lapses were determined for each test and time point. The PVT-3 elicited significantly faster response speeds than the other two tests (p < 0.01), while the PVT-5 and PVT-10 were not different. The PVT-10 resulted in more lapses than the PVT-5, followed by the PVT-3, with all tests being significantly different to each other (p < 0.01). In conclusion, while the PVT-5 and PVT-10 were generally similar for response speed, the PVT-3 did not produce results comparable with the PVT-10 for response speed, lapses or errors, and should therefore not be used interchangeably. Further research is required to determine whether the shorter tests are a suitable replacement for the PVT-10 in professional basketball players.